ANALISIS PENGARUH STOCK SPLIT TERHADAP HARGA SAHAM PADA PERUSAHAAN GO PUBLIC DI BURSA EFEK INDONESIA (PERIODE 2007 S.D. 2011) - Yan Noviar Nasution; Herdiyana Herdiyana (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2012)
ABSTRACT Stock splits is cosmetic or the actions are not has an economic of value that should not change the stock price. However some researchers conclude that stock splits has a significant influence on stock price changes. stock splits performed on the basis of two theories. According to the Trading Range Theory, stock prices High is the driving force for the company to conduct a stock splits with the hope to increasing the liquidity of stock trading, placing these shares at the optimal trading range will cause the more investors who invest. Signaling theory states that stock splits is a carrier of information about the performance and prospects companies to the market. This study aims to obtain empirical about evidence the impact of stock splits on stock prices relative The research data was taken from the 30 companies in Indonesia Stock Exchange who doing stock splits during the years 2007 until 2011. Stock price data of each company for five days before and five days after the stock splits. Analysis techniques are used to test the hypothesis is Wilcoxon Signed Ranked Test (Wilcoxon Signed Rank Test) with a confident level of 95 percent (? = 0.05). Based on the analysis has been carried out on 30 issuers for five days before and five days after the stock splits in the year 2007-2011 in Indonesia Stock Exchange can be concluded that based on test results, either per issuer or average and overall, it showed there is a different of stock prices relative before and after stock splits. Key words: Solving stock, Signaling theory, Trading range theory